Brunet wieczorowa pora - Bareja, Stanisław (Poland : Film Studio Pryzmat, 1976)
A satirical comedy and a parody of English crime stories. Michał - a modest editor, has got rid of his wife and kids for the weekend and is trying to relax in his house on the outskirts of Warsaw. His quiet evening is only disturbed by the chance prediction made by a Gypsy woman, that the same evening he will murder a mysterious "brunet". At first he does not take this seriously, but when all the predictions made by the woman start coming true – he finds a lost watch, lottery numbers she gave were drawn. Michał leaves the house, hoping to escape his grim destiny, but soon a body is found there. All the evidence points to Michał as the murderer. Together with a friend, Michał sets up a trap for the real murderer. Soon it turns out who the Gypsy woman really was…
Duration: 01:30:00
Keywords: Fiction films